Limnology of the Red Lake, Romania An Interdisciplinary Study - Romanescu, Gheorghe; Stoleriu, Cristian Constantin; Enea, Andrei (Springer Netherlands : Imprint: Springer, 2013)
The Red Lake is a natural barrier lake at the foot of the Hasmasu Mare Mountains in the Eastern Carpathian Range in Romania. It was formed when the Bicaz River was blocked by a natural dam resulting from two landslides during an extreme heavy storm in 1837. This book presents an interdisciplinary and comprehensive study on the physical, chemical, geographical and ecological aspects of Red Lake (Lacu Rosu). The first three chapters cover the formation and geological setting and its relationship with the Bicaz Gorges-Haghimas national park. Subsequent chapters present the sedimentological, morphological and hydrological evolution of this unique natural laboratory and climatological setting. The final chapters deal with ecological aspects of Red Lake waters and adjacent ecosystems such as wetlands and water resource management issues.